High detection of virulence factors by Candida species isolated from bloodstream of patients with candidemia. (December 2020) - Nouraei, Hasti; Pakshir, Keyvan; ZareShahrabadi, Zahra; Zomorodian, Kamiar
Abstract: Objective: Candida species are the normal inhabitants of the skin and mucosa that cause a wide range of debilitating diseases in immunocompromised patients and other susceptible individuals. The present study aimed to evaluate the production of exoenzymes and the biofilm formation capacity of Candida species isolated from candidemia. Materials and methods: In this study, a total of 100 stock Candida species isolates consist of 50 Candida albicans and 50 non- Candida albicans Candida species (24 C. glabrata, 15 C. parapsilosis, 5 C. dubliniensis, 3 C. tropicalis, 2 C. krusei and 1 C. fabianii ) which previously were recovered from patients with candidemia were used. The enzymatic activity tests for hemolysin, proteinase, and phospholipase were performed by using blood Sabouraud dextrose agar, bovine serum albumin medium and egg yolk agar, respectively. Biofilm formation was determined by microplate assay method. Result: All of the Candida albicans species could produce hemolysin. The predominant enzyme activity of species included strong and very strong levels of phospholipase, proteinase and hemolysin activity were belonged to Candida albicans isolates. There were statistically significant differences in hemolysin (P < 0.001), proteinase (P = 0.003) and phospholipase (P < 0.001) activity between two groups of albicans and non- albicans species. The biofilm formation was seen in 30 (60%) of C. albicans and 49 (98%) of non- C. albicans species. There was significant statistical differences between the two groups of isolates in biofilm formation (P < 0.001). Conclusion: It is clear that Candida species have ability to produce several enzymes as virulence factors to contribute its pathogenicity. There were significant differences in virulence factors between the two C . albicans and non- C. albicans group. The ability for biofilm formation and producing exo-enzyme were an important virulence factors in Candida species isolates. This differences found in this report might have role in severity of disease caused by different species. Highlights: This is the first report of exoenzymes profile and biofilm formation in causative aganet of candidemia in Shiraz, Iran. Exo-enzymes activity revealed significant differences between two groups of C. albicans and non- albicans species group. Biofilm formation was seen in 60% of C. albicans and 98% of non albicans species with significant statistical differences. More than 82% of the Candida albicans isolates exhibited hemolysin as strongly positive.